CERRADO SMALL MAMMALS: abundance and distribution of marsupials, lagomorphs, and rodents in a Neotropical savanna - André Mendonça; Alexandre R. Percequillo; Nicholas F. Camargo; Juliana F. Ribeiro; Alexandre R. T. Palma; Leonardo C. Oliveira; Edeltrudes M. V. C. Câmara; Emerson M. Vieira (Ecology, 2018)
Patterns in distribution and local abundance of species within a biome are central concerns in ecology and allow the understanding of the effects of habitat loss on rates of species extinction; provide support for the creation and management of reserves; and contribute to the identification and quantification of the processes that allow niche partitioning by species. However, despite the importance in the conservation and management of the ecosystems, most systematized information on the abundance and distribution of small mammals is restricted to the northern hemisphere or forest ecosystems. For tropical biomes, an important part of this information remains dispersed and difficult to access in the form of theses, technical reports, or unpublished data sets. Here we present a comprehensive data set of abundance and richness of small mammals in the Cerrado, the largest Neotropical savanna. This data set includes 2,599 records of 446 sites from 96 studies. More than 50% of references in this data set are peer‐reviewed journal articles, but 45.78% of communities were compiled from theses. The data set comprises 24,283 individuals of 55 genera and at least 118 species of small mammals including 29 marsupials, two lagomorphs (one exotic), and 87 rodents (three exotic). Local species richness ranged from 1 to 26 species (5.82 ± 3.55, average species richness ± SD ). We observed hyperdominance of a few species; the 10 most abundant species in this data set represented 60.19% of all recorded individuals. The hairy‐tailed bolo mouse ( Necromys lasiurus ) represented over than 20% of all individuals and occurred at more than 50% of sites. Furthermore, we identified 18 environments, 16 native vegetation types, and 2 anthropic environments. Typical savanna and gallery forest were the most frequently sampled vegetation types (comprising 46.94% of all sampled sites) and the most speciose ones (57 species for typical savanna and 53 species for gallery forest). The information contained in this data set can be used to analyze ecological questions such as the relationship between local abundance and regional distribution, the relevance of local and regional factors to community structuring, and the role of phylogenetic mechanisms in community assemblage. It can also be useful in conservation efforts in this biodiversity hotspot. No copyright, proprietary, or cost restrictions apply. Please cite this paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.